Review on Nanoemulsion Based Nanogel for Fungal Infection - Gupta, Sanjiv Kumar; Chaubey, Neelesh (International Journal of Pharmaceutical Investigation, 2025)
Nanoemulsion-based nanogels have emerged as a promising approach for treating fungal infections due to their unique properties. Nanoemulsions are fine oil-in-water or water-in-oil dispersions stabilized by surfactants, characterized by their small droplet size, which enhances the solubility and bioavailability of hydrophobic drugs. When integrated into nanogels, these nanoemulsions provide a stable, gel-like medium that ensures prolonged retention and controlled release of antifungal agents at the infection site. The nanogel matrix not only offers a localized treatment, reducing systemic side effects, but also protects the encapsulated drugs from degradation, enhancing their efficacy. Additionally, the high surface area and small size of nanoemulsion droplets facilitate better penetration into fungal biofilms and deeper layers of infected tissues, improving therapeutic outcomes. Recent studies have demonstrated the effectiveness of nanoemulsion-based nanogels in delivering antifungal agents like fluconazole, amphotericin B, and clotrimazole, showing enhanced antifungal activity compared to conventional formulations. These nanogels exhibit superior mucoadhesive properties, making them suitable for treating mucosal infections. In conclusion, nanoemulsion-based nanogels represent a significant advancement in antifungal therapy, offering improved drug delivery, enhanced antifungal efficacy, and reduced adverse effects, thus holding great potential for the effective management of fungal infections.
Keywords: Antifungal Agents; Hydrophobic Drugs; Mucoadhesive; Nanoemulsions